2018
DOI: 10.1177/1091581817750560
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Oxidative, and Physiological Changes Caused by Acute Exposure of Fentanyl and Its 3 Analogs in Rodents

Abstract: Synthesis and bioefficacy of fentanyl and its 8 new 1-substituted analogs (1-8) were earlier reported by us. Of these 8 compounds, N-(1-(2-phenoxyethyl)-4-piperidinyl)propionanilide (2), N-isopropyl-3-(4-( N-phenylpropionamido)piperidin-1-yl)propanamide (5), and N- t-butyl-3-(4-( N-phenylpropionamido)piperidin-1-yl) propanamide (6) were found to be more effective and less toxic compared to fentanyl. The present study reports the acute effect of fentanyl (0.50 Median Lethal Dose (LD); intraperitoneal) and its 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…34 The mechanical stimulation did not affect animals treated with the range dose 1–15 mg/kg at 245 min (Figure 2 C and D). This effect could be related to the respiratory depression seen in mice 15,35 and/or the muscle rigidity as reported in rats 36 and in cases of fentanyl users. 37…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…34 The mechanical stimulation did not affect animals treated with the range dose 1–15 mg/kg at 245 min (Figure 2 C and D). This effect could be related to the respiratory depression seen in mice 15,35 and/or the muscle rigidity as reported in rats 36 and in cases of fentanyl users. 37…”
Section: Discussionmentioning
confidence: 71%
“…34 The mechanical stimulation did not affect animals treated with range dose 1-15 mg/kg at 245 min (Figure 2 C and D). This effect could be related to the respiratory depression seen in mice 15,35 and/or the muscle rigidity as reported in rats 36 and in cases of fentanyl users. 37 Previous studies carried out both in vivo and in vitro models 38,39 showed that fentanyl is mainly metabolized to norfentanyl by N-dealkylation at the piperidine ring; only less than 1% is converted by alkyl hydroxylation or combined N-dealkylation and hydroxylation to hydroxyfentanyl and hydroxynorfentanyl.…”
Section: Discussionmentioning
confidence: 78%
“…Prior clinical data show that high doses of morphine induce a marked but transient reduction in urinary flow rate and a robust decrease in glomerular filtration rate (Mercadante and Arcuri, 2004). Both fentanyl and carfentanil induce substantial decreases in mean arterial pressure in rodents (Wong et al, 2017;Yadav et al, 2018), and it is tempting to speculate this effect could contribute to reduction in urine output. Regardless of the mechanisms involved, we hypothesize that nonlinear accumulation of carfentanil in humans could exacerbate the inherent dangers of this ultrapotent opioid agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Blood gas analysis was conducted as described . Male mice weighing 25–30 g received subcutaneously administered saline or OFP011 and then anesthetized with isoflurane.…”
Section: Methodsmentioning
confidence: 99%